PEMANFAATAN LIMBAH PADAT KOMPOS KOTORAN TERNAK DALAM MENINGKATKAN DAYA DUKUNG LINGKUNGAN DAN BIOMASA TANAMAN KACANG HIJAU (Vigna radiate L.) VARIETAS VIMA 1 - Nenobesi, Djonius; Mella, W.; Soetedjo, P. (Bumi Lestari; Vol 17 No 1 (2017)DO - 10.24843/blje.2017.v17.i01.p08, 2017)
Animal sluge may a positively impact to environment if it utilize properly as organic fertilizer. Main aims of research was to determine effect of solid composted animal sludge to improve environmental capability and biomass of mung bean. The research had been conducted from June to August 2016. The research was designed to Split Plot Design in which main variable were A=composted chicken manure, B=composted cow manure, C=composted of slurry, sub variable were D0=no fertilizer, D1=15t/ha of fertilizer, D2= 30 t/ha of fertilizer, D3= 45 t/ha of fertilizer. All data were analyzed by analysis of variant thereafter by using Duncan Multiple Range test at 5% level. Result of the research showed that a treatment of composted of slurry interacted by dosage of 45 t/ha effect significantly to physical characteristic of Vertisol (bulk density), chemical characteristic of Versitol (bH, P, K, C organic), number of colonies bacteria,yield ofmung bean (1,17 t/ha), and water use efficiency (9,85 kg/ltr).